Early Music History: Studies in Medieval and Early Modern Music 1-12; 22 - Fenlon, Iain (Cambridge Cambridge University Press, 1981)
Early Music History is devoted to the study of music from the early Middle Ages to the end of the seventeenth century. It demands the highest standards of scholarship from its contributors, all of whom are leading academics in their fields. It gives preference to studies pursuing interdisciplinary approaches and to those developing novel methodological ideas. The scope is exceptionally broad and includes manuscript studies, textual criticism, iconography, studies of the relationship between words and music and the relationship between music and society.
Keywords: Middle Ages (500-1400); Renaissance (1400-1600); Music history; Musical analysis